A light-weight, high-sensitivity particle spectrometer for PM2.5 aerosol measurements. Issue 1 (2nd January 2016) - Gao, R. S.; Telg, H.; McLaughlin, R. J.; Ciciora, S. J.; Watts, L. A.; Richardson, M. S.; Schwarz, J. P.; Perring, A. E.; Thornberry, T. D.; Rollins, A. W.; Markovic, M. Z.; Bates, T. S.; et al.
ABSTRACT: A light-weight, low-cost optical particle spectrometer for measurements of aerosol number concentrations and size distributions has been designed, constructed, and demonstrated. The spectrometer is suitable for use on small, unmanned aerial vehicles (UAVs) and in balloon sondes. The spectrometer uses a 405 nm diode laser to count and size individual particles in the size range 140–3000 nm. A compact data system combines custom electronics with a single-board commercial computer. Power consumption is 7W at 9–15 V. 3D printing technology was used in the construction of the instrument to reduce cost, manufacturing complexity, and weight. The resulting Printed Optical Particle Spectrometer (POPS) instrument weighs about 800 g with an approximate materials cost of 2500 USD. Several POPS units have been constructed, tested in the laboratory, and deployed on UAVs. Here we present an overview of the instrument design and construction, laboratory validation data, and field engineering data for POPS.